A qualitative study of contemporary secure mental health services: women service users' views in England. Issue 5 (3rd September 2019) - Walker, Tammi; Shaw, Jenny; Edge, Dawn; Senior, Jane; Sutton, Matthew; Meacock, Rachel; Wilson, Hannah; McNair, Louisa; Mitchell, Heather; Gutridge, Kerry; Abel, Kathryn M.
ABSTRACT: Women's Enhanced Medium Secure Services (WEMSS) was a concept borne out of findings that an inappropriate number of women were being held in high secure services, despite not fulfilling high secure criterion. A qualitative study of women service users' views of living in WEMSS and comparator medium secure services (MSS) in the UK is presented. Sixteen service users participated in semi-structured interviews. Thematic analysis identified four main themes: experiences of current placement versus previous placements, relationships with staff, challenges of living with other women and having a voice – being involved in care and treatment. The accounts reported suggest that women in WEMSS and standard MSS have very similar experiences of their service, relationships with staff, living with other women and involvement in care. This qualitative study suggests that women in WEMSS and comparable women in MSS have very similar perspectives on what works well in their current services and what is important to them. The main differences between WEMSS and MSS women's accounts were in relation to the amount of pre-transfer information they received and levels of staff support. Implications for practice are discussed, including service-user empowerment addressing barriers to relational security.